2022
DOI: 10.3390/pharmaceutics14030619
|View full text |Cite
|
Sign up to set email alerts
|

STOP Pain Project—Opioid Response in Pediatric Cancer Patients and Gene Polymorphisms of Cytokine Pathways

Abstract: Moderate to severe cancer pain treatment in children is based on the use of weak and strong opioids. Pharmacogenetics play a central role in developing personalized pain therapies, as well as avoiding treatment failure and/or intolerable adverse drug reactions. This observational study aimed to investigate the association between IL-6, IL-8, and TNFα genetic single nucleotide polymorphisms (SNPs) and response to opioid therapy in a cohort of pediatric cancer patients. Pain intensity before treatment (PIt0) sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…TNF was much lower in patients with severe pain, while IL-6 and substance P levels trended downward [ 100 ]. In their observational study, Crescioli et al found that the SNPs of IL6 (rs1800797) and TNF (rs1800629) may serve as possible indicators of baseline pain severity and opioid dosage requirements among pediatric cancer patients [ 40 ]. In a pioneer study, Chang et al investigated the putative participation of cancer-related lncRNAs in endometriosis and detected genetic variants in UCA1, a lncRNA serving as a miRNA sponge, which can be found in endometriosis development and is potentially associated with infertility via regulating lipogenesis [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNF was much lower in patients with severe pain, while IL-6 and substance P levels trended downward [ 100 ]. In their observational study, Crescioli et al found that the SNPs of IL6 (rs1800797) and TNF (rs1800629) may serve as possible indicators of baseline pain severity and opioid dosage requirements among pediatric cancer patients [ 40 ]. In a pioneer study, Chang et al investigated the putative participation of cancer-related lncRNAs in endometriosis and detected genetic variants in UCA1, a lncRNA serving as a miRNA sponge, which can be found in endometriosis development and is potentially associated with infertility via regulating lipogenesis [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with at least one copy of the A allele had a significantly lower risk of achieving an NRS pain intensity score of more than 4 points. The SNP rs1800795 for IL-6 may also provide some indication of personal sensitivity to pain stimuli, as the same study revealed that carriers of the G/G genotype in SNP rs1800795 have a higher risk of pre-treatment pain intensity (PI t0 > 4 and ΔVAS > 2) compared to carriers of even one C allele [21].…”
Section: Othersmentioning
confidence: 93%
“…A similar relationship was also described for the TNFα rs1800629 SNP -daily and total doses of morphine or other opioids per MED were statistically significantly higher (p = 0.010 and p = 0.031, respectively) in patients with the G/G genotype compared to others. This leads to the conclusion that SNPs for IL-6 and TNF-α may also, in addition to the more extensively studied SNPs described above, be potential indicators of initial pain intensity in oncology patients and, at the same time, a marker of demand for opioids in a particularly important, but less studied, group of paediatric oncology patients [21].…”
Section: Othersmentioning
confidence: 98%
See 1 more Smart Citation